La percepción de los docentes y la IA en la educación superior: un análisis cualitativo - Guerrero López, Carlos Alberto (2025)
In Peru, spending on education represents 17.9% of GDP, but young people still prefer university education over technical-productive education, despite the high demand for technical labor. Of the total number of students, 51% are women and 25% are in poverty, with a majority enrolled in private universities (82%) and popular careers such as Administration, Law, and Engineering (INEI, 2022). This study explores the perceptions of 20 teachers from three Peruvian universities about AI, focusing on its impact on teaching, personalization of learning, and operational efficiency. Using a qualitative approach based on grounded theory, the interviews reveal optimism about the potential of AI, but highlight barriers such as lack of infrastructure, insufficient training, and privacy concerns. The results suggest that targeted investments, professional development, and appropriate policies are key to equitable adoption of AI. This research shows how teacher perceptions influence AI adoption and proposes recommendations to improve its implementation in higher education.